2007
DOI: 10.1055/s-2007-981548
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chrysin and Natural Coumarins on UGT1A1 and 1A6 Activities in Rat and Human Hepatocytes in Primary Culture

Abstract: Flavonoids and coumarins are naturally occurring compounds that are widely distributed in vegetables and have a broad pharmacological activity. Inducibility of UDP-glucuronosyltransferases (UGTs) by xenobiotics is well documented and can be considered beneficial for health. In particular, UGT1A1-dependent bilirubin conjugation plays a critical role in the detoxification of neurotoxic bilirubin and phenobarbital-mediated UGT1A1 induction therapy is commonly used in the treatment of unconjugated hyperbilirubinem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…The importance of investigating such a potential health concern is even more evident in view of the fact that the intake of high doses of purified NAhRAs is being promoted as healthy food supplements. The interest in this type of food supplements is based on the observation that some identified NAhRAs from vegetables and fruits, like indole‐3‐carbinol in cruciferous vegetables, furocoumarins in citrus fruits and flavonoids such as chrysin, baicalein and cantharidin in vegetables and herbs can show health‐promoting effects, especially as tumor suppressors and are thought to be an important cause for the observed beneficial effects of vegetable‐ and fruit‐enriched diets 3, 61–63. It is remarkable that the proposed mechanism of anti‐tumor activity is also based on the AhR activation, and the subsequent induction of phase I and II biotransformation enzymes like CYP1A1 , CYP1A2 and UDPGT1A6 64, 65.…”
Section: Risk–benefit Analysis Of Dietary Phytochemicalsmentioning
confidence: 99%
“…The importance of investigating such a potential health concern is even more evident in view of the fact that the intake of high doses of purified NAhRAs is being promoted as healthy food supplements. The interest in this type of food supplements is based on the observation that some identified NAhRAs from vegetables and fruits, like indole‐3‐carbinol in cruciferous vegetables, furocoumarins in citrus fruits and flavonoids such as chrysin, baicalein and cantharidin in vegetables and herbs can show health‐promoting effects, especially as tumor suppressors and are thought to be an important cause for the observed beneficial effects of vegetable‐ and fruit‐enriched diets 3, 61–63. It is remarkable that the proposed mechanism of anti‐tumor activity is also based on the AhR activation, and the subsequent induction of phase I and II biotransformation enzymes like CYP1A1 , CYP1A2 and UDPGT1A6 64, 65.…”
Section: Risk–benefit Analysis Of Dietary Phytochemicalsmentioning
confidence: 99%
“…To date, there is a paucity of research on the biological activity of avicennol, which has been previously identified in Z. elephantiasis Macfad (Gray et al, 1977). Recent work with avicennol reports an induction of UDP-glucuronosyltransferases (UGT), specifically UGT1A1, which detoxifies xenobiotics (Chlouchi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…BNF is an inducer of various detoxification enzymes, such as CYPs 450 and uridine-5'-diphosphoglucuronosyltransferases (UGTs) [167].…”
Section: Detoxification Enzymesmentioning
confidence: 99%